1997
DOI: 10.1007/s002239900208
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Cortical and Trabecular Bone Loss as Quantified by Peripheral Computed Tomography (pQCT) at the Ultradistal Radius in Aging Women

Abstract: Abstract. Peripheral quantitative computed tomography (pQCT) allows the separate determination of cortical and trabecular bone mineral density in the peripheral skeleton. This cross-sectional study was designed to examine the effects of healthy aging on pQCT measurements at the ultradistal radius. In a well-defined sample of 129 community-based women, aged 70-87 years, the differences in cortical and trabecular density over the age range were equivalent to losses of −0.41% and −0.65% per year, respectively. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 45 publications
(40 reference statements)
5
38
2
Order By: Relevance
“…In the present study, grip strength was significantly correlated with vBMD, Ct.Ar, Ct.Th and bone strength index. However, Boonen et al reported that grip strength was significantly related to cortical, but not to trabecular density in 129 community based women by radial pQCT [29]. These discrepancies might be caused by the relatively small number of subjects in their study.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, grip strength was significantly correlated with vBMD, Ct.Ar, Ct.Th and bone strength index. However, Boonen et al reported that grip strength was significantly related to cortical, but not to trabecular density in 129 community based women by radial pQCT [29]. These discrepancies might be caused by the relatively small number of subjects in their study.…”
Section: Discussionmentioning
confidence: 77%
“…(8) The lack of anabolic properties of DHT on lean body mass could contribute to the finding that even high doses of DHT had no impact on cortical bone, a bone compartment known to be more dependent on muscle function. (16) In addition to its failure to stimulate lean body mass, DHT-again in contrast to testosterone (8) -decreased concentrations of serum IGF-I, a growth factor known to stimulate bone formation and muscle metabolism. To the best of our knowledge, a DHTinduced decrease of IGF-I has not been reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Boonen et al (40) found no significant association between calcium intake and volumetric bone density. In an intervention study by Rüegsegger et al, (41) calcium compounds were able to slow down trabecular bone loss from both the distal radius and the distal tibia.…”
Section: Uusi-rasi Et Almentioning
confidence: 95%
“…The two studies (29,40) already mentioned did not evaluate bone size. In our previous study with DXAestimated bone variables, we found calcium intake to be associated positively with bone width and estimated bone strength in the diaphyses of the radius.…”
Section: Uusi-rasi Et Almentioning
confidence: 99%